Contribution of BKCa channels to vascular tone regulation by PDE3 and PDE4 is lost in heart failure. Issue 1 (23rd June 2018) - Idres, Sarah; Perrin, Germain; Domergue, Valérie; Lefebvre, Florence; Gomez, Susana; Varin, Audrey; Fischmeister, Rodolphe; Leblais, Véronique; Manoury, Boris
Abstract: Aims: Regulation of vascular tone by 3′, 5′-cyclic adenosine monophosphate (cAMP) involves many effectors including the large conductance, Ca 2+ -activated, K + (BKCa ) channels. In arteries, cAMP is mainly hydrolyzed by type 3 and 4 phosphodiesterases (PDE3, PDE4). Here, we examined the specific contribution of BKCa channels to tone regulation by these PDEs in rat coronary arteries, and how this is altered in heart failure (HF). Methods and results: Concomitant application of PDE3 (cilostamide) and PDE4 (Ro-20-1724) inhibitors increased BKCa unitary channel activity in isolated myocytes from rat coronary arteries. Myography was conducted in isolated, U46619-contracted coronary arteries. Cilostamide (Cil) or Ro-20-1724 induced a vasorelaxation that was greatly reduced by iberiotoxin (IBTX), a BKCa channel blocker. Ro-20-1724 and Cil potentiated the relaxation induced by the β-adrenergic agonist isoprenaline (ISO) or the adenylyl cyclase activator L-858051 (L85). IBTX abolished the effect of PDE inhibitors on ISO but did not on L85. In coronary arteries from rats with HF induced by aortic stenosis, contractility and response to acetylcholine were dramatically reduced compared with arteries from sham rats, but relaxation to PDE inhibitors was retained. Interestingly, however, IBTX had no effect on Ro-20-1724- and Cil-induced vasorelaxations in HF. Expression of the BKCa channel α-subunit, of a 98 kDa PDE3A and of a 80 kDa PDE4D were lower in HF compared with sham coronary arteries, while that of a 70 kDa PDE4B was increased. Proximity ligation assays demonstrated that PDE3 and PDE4 were localized in the vicinity of the channel. Conclusion: BKCa channels mediate the relaxation of coronary artery induced by PDE3 and PDE4 inhibition. This is achieved by co-localization of both PDEs with BKCa channels, enabling tight control of cAMP available for channel opening. Contribution of the channel is prominent at rest and on β-adrenergic stimulation. This coupling is lost in HF.